Skin and bones [large type] : and other Mike Bowditch short stories - Doiron, Paul (Doiron, Paul. Mike Bowditch mystery series., 2025)
"... A collection of eight gripping original short stories in the bestselling Mike Bowditch series including one brand new, never-before-published story. In the first three entries, legendary Maine woodsman and bush pilot Charley Stevens draws Mike into some of the strangest cases of his storied career: extolling on the dangers awaiting rookie game wardens, a gruesome case involving a bat with rabies, and a visiting hunter who goes missing in the middle of a snowstorm and may not want to be found. Then Mike is confronted with his own baffling cases: he discovers a dead body whose driver's license claims he is none other than Mike Bowditch himself. He tracks down a sinister prowler who turns a couple's dream vacation home into a nightmare. An investigation into the killing of a bald eagle unearths an old case of a missing young man whose physically abusive brother might have murdered him. And then Mike must hunt down a killer who uses the unlikeliest of murder weapons: rattlesnakes. And in the final, brand-new short story, Sheep's Clothing, Mike suspects there's more to a grisly murder-suicide than meets the eye."--